Higher education funding in Germany: A distributional lifetime perspective - Dominik Hügle (Freie Universität Berlin, School of Business & Economics, 2020)
This paper analyzes higher education funding in Germany from a distributional perspective. For this, I first compare the quantitative importance of different funding instruments, from free tuition to subsidized health insurance for students. I show that free tuition is, by far, the most important instrument. Then, I take a lifetime perspective and assess how individuals of different expected lifetime incomes benefit from higher education funding. I distinguish between different fields of study as there are large differences in both the expected lifetime earnings of graduating from a specific field and the social cost of tuition associated with each field. Finally, I focus exclusively on the instrument of subsidized tuition and simulate the introduction of different tuition fee schemes with income-contingent loans. While the distributional effects would be sizable in absolute terms, I estimate that they would cause few individuals to change their educational decisions.
urn:nbn:de:kobv:188-refubium-29186-4
Keywords: C53; I22; I23; 330; Higher education; Education finance; Dynamic microsimulation